Perspectives of Organic and Perovskite‐Based Spintronics (Advanced Optical Materials 14/2021). Issue 14 (9th July 2021) - Privitera, Alberto; Righetto, Marcello; Cacialli, Franco; Riede, Moritz K.
Abstract : In Perspective number 2100215, Alberto Privitera and co‐workers demonstrate how the use of two emerging optoelectronic materials, namely organic semiconductors and halide perovskites, will offer exciting ways to manipulate the spin, charges and photons in new spin/opto‐electronic devices. The first progress in this field is reviewed and current challenges are outlined along with proposing possible approaches to overcome them. The unique synergy between these two classes of materials has the potential to revolutionize several technological applications, for example data processing and storage, quantum computing, lighting, energy harvesting, sensing, and healthcare.